PERANAN LINGKUNGAN KERJA DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI HONORER PADA FAKULTAS SAINS DAN TEKNOLOGI UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU - Risman, Risman (Komunitas Manajemen Kompetitif, 2024)
This research was conducted at the Faculty of Science and Technology, Sultan Syarif Kasim Riau State Islamic University which is located at Jl.H.R Subrantas No.155, KM 15 Pekanbaru. The sample was taken as many as 35 people. Data analysis in this study used descriptive and quantitative analysis methods. Descriptive is comparing between the actual reality with theories that have to do with the problem in order to draw a conclusion and tabulated in the form of frequency distribution tables. While the quantitative method of research is based on data that can be calculated to produce a solid assessment. The results of simple linear regression research in this study are Y = 860 + 0.906 X. By using the t test, the t table value is 1.985 and the tcount value is 7.429, meaning that the tcount = 7.429> t table = 2.032, which means that the employee work environment affects employee performance at the Faculty of Science and Technology, Sultan Syarif Kasim State Islamic University, Riau, the influence is 62.2%. Keywords: Work Environment and Performance